Application of Ultra Wideband Signal with High Repetition Rate in Forward Scatter Multi-Static Radar System - E. A. Kolokoltsev; A. V. Myakinkov (Известия высших учебных заведений России: Радиоэлектроника)
The paper deals with the problem of detection of slow-moving ground targets in the multi-static ultra wideband forward-scatter radar. The existing methods of ground target detection cannot simultaneously provide high efficiency in conditions of clutter and required resolution. The author proposes algorithms of UWB signal forming and processing which provides the increase of the coverage when detecting ground targets and high range resolution. The considered approach is based on the use of ultra-wideband signal with high repetition rate. Such signal is generated by means of combination of a number of sequences with different repetition periods. Integration of target reflected signal at the receiving side is performed in separate channels for each sequence. After that, the results of integration are summed up coherently. This approach allows to disambigue range measurements and increase total energy of the signal. The coverage of forward-scatter radar when using UWB probing signal is analyzed. The estimation of UWB FSR coverage is obtained for the case when different numbers of quasi-orthogonal sequences with different repetition periods are used for complex probing signal formation. It is shown that the increase of the number of sequences allows the reduction of the required number of positions when keeping the controlled perimeter or the increase of controlled perimeter with the same number of positions.